(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2024)
This article presents analyzes of the study of innovative trends in the entrepreneurial sector of Uzbekistan, the role of innovation processes in the development of entrepreneurship, their impact on the country’s economy, and their role in increasing the income of the population. Also, the article contains information about the innovations and successes in this direction in Uzbekistan’s innovative activities.